Ultrasonographic and morphological sequelae to repeated testicular biopsies in stallions in relation to the lateral branching of the testicular artery. (3rd May 2016) - Pozor, M. A.; Zambrano, G. L.; Runcan, E. E.; Kelleman, A. A.; Macpherson, M. L.
Summary: The objectives of this study were to investigate the sequelae to repeated testicular biopsies in stallions and to determine if arterial injuries can be prevented. This study was part of a larger project focused on the antispermatogenic effects of an oral contraceptive compound, RTI‐4587‐073(l), which was given to 3 mature Miniature horse stallions, while another 3 received a placebo treatment. Testicular biopsies were taken once before treatment and 3 times after treatment. They were obtained from alternating testes, 2 procedures per testis, 2 samples each time, using a 18 gauge split‐needle core biopsy instrument (penetration depth: 22 mm). Colour Doppler ultrasonography was performed prior to the procedure to detect and thus avoid lateral branches of the testicular artery. Testicular parenchyma was evaluated ultrasonographically just before, and 2–6 h, 3 days and weekly after the biopsies were obtained. Changes in testicular volumes and semen parameters were monitored. All stallions were then castrated and the testes were evaluated for any gross pathology. There was no major scrotal swelling or gross haemorrhage after the procedures. Only mild, focal lesions were found in the testicular parenchyma 3 and 7 days after taking the biopsies. Three lateral branches of the testicular arteries were punctured, but there was no evidence of significant bleeding or other complications associated with these injuries. We conclude that repeated testicular biopsies may be taken from stallions without causing major complications, regardless of a presence or absence of the lateral branches of the testicular artery. Furthermore, we conclude that using colour Doppler ultrasonography to detect the lateral branches of the testicular arteries is unreliable; however, puncturing these vessels during a biopsy procedure does not necessarily result in significant haemorrhage.